2019
DOI: 10.1016/j.neulet.2018.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Reduced interleukin 1A gene expression in the dorsolateral prefrontal cortex of individuals with PTSD and depression

Abstract: The inflammatory system has been implicated in the pathophysiology of a variety of psychiatric conditions. Individuals with PTSD, depression, and other fear-and anxiety-related disorders exhibit alterations in peripheral circulating inflammatory markers, suggesting dysregulation of the inflammatory system. The relationship between inflammation and PTSD has been investigated almost exclusively in the periphery, and has not been extensively explored in human postmortem brain tissue. Interleukins (ILs) represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…Lastly, the literature selection criteria of the current review excluded a number of studies that provided significant evidence with regards to the pathophysiology of PTSD due to its comorbid sample population. As PTSD has a prevalence of comorbidity with a vast number of other chronic diseases [7][8][9]31,112,113], the segregation between PTSD with other medical conditions may limit our understanding of its pathophysiology if observed independently. Further research that investigate the pathogenesis of PTSD through a multi-level approach of inflammatory responses, clinical symptoms, and brain structural and functional changes, may help determine the detailed underlying pathway of PTSD, and open up novel strategies of assessment and intervention for the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the literature selection criteria of the current review excluded a number of studies that provided significant evidence with regards to the pathophysiology of PTSD due to its comorbid sample population. As PTSD has a prevalence of comorbidity with a vast number of other chronic diseases [7][8][9]31,112,113], the segregation between PTSD with other medical conditions may limit our understanding of its pathophysiology if observed independently. Further research that investigate the pathogenesis of PTSD through a multi-level approach of inflammatory responses, clinical symptoms, and brain structural and functional changes, may help determine the detailed underlying pathway of PTSD, and open up novel strategies of assessment and intervention for the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…These regions were selected based on findings from functional and structural imaging studies of PTSD suggesting their involvement in the neurobiology of the disorder (see e.g., [34]). A detailed description of the donor identification, postmortem diagnostic assessment procedures, and tissue extraction and processing is presented elsewhere [24,35] and in Additional file 1.…”
Section: Ptsd Brain Bankmentioning
confidence: 99%
“…Gene expression changes in the somatostatin and acetylcholine systems, metallothionein proteins, metal‐ion binding proteins, and the MAPK/ERK signaling have been, on the other hand, described in bipolar patients . Finally, only few transcriptomic studies on PTSD patients can be found in literature and they point at mitochondrial disfunction and alterations in the immune system as PTSD transcriptional signatures. However, most of these studies have been focused solely on male patients or did not stratify by sex.…”
Section: Human Studiesmentioning
confidence: 99%